Peran Panti Asuhan Yayasan Rumah Bakti Kasih Anak Indonesia dalam Membentuk Karakter Anak Panti - Tiara Fany Chintia Silitonga; Wulan Purnama Sari Simatupang; Loise Chisanta Ginting; Muhammad Aimar Zaidan; Harrys Cristian Vieri (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
Children are an important asset for the future of the nation.  As the next generation of the nation, children should have their needs met both physically and mentally.  An orphanage is a professional service institution that is responsible for providing care and replacement services for neglected children.  With this orphanage, abandoned children can be protected and sheltered by responsible and professional people who are able to manage the orphanage properly.  The parenting style applied at the Rumah Bakti Kasih Anak Indonesia Orphanage uses a family approach, namely by replacing the role and position of parents, which is applied according to the conditions of foster children, using a democratic parenting pattern.  Panting helps children get an education and get character education that they must get from an early age. MHowever, of course there are disadvantaged children whose needs are difficult to meet, for example, children who have become orphans. Therefore, the orphanage as one of the social services exists to ensure the needs of these disadvantaged children. The existence of this research aims to review the social services provided by the Rumah Bakti Kasih Anak Indonesia Foundation both in quality and quantity.  This research collected data using literature studies, and observations through direct interviews with the orphanage administrators. And from the results of this survey we found that the orphanage at the Rumah Bakti Kasih Anak Foundation was quite good at shaping the character of the orphans